Projeto de semáforo sustentável alimentado por sistema híbrido - Borges, Hellisson de Castro Freitas Barbosa (Universidade Federal do Tocantins, 2019)
The lack of electricity, coming from the public network, that feeds the traffic lights cause disorder on the car flow, due to this, an implementation of a support system on blackouts with the use of a battery bank and solar energy becomes viable and tangible, taking in consideration the energetic potential of the state. The viability of using solar energy on the state of Tocantins it's proven by its levels of solar irradiation. Therefore, sustainable traffic lights alternative, that uses clean and renewable energies appears before the rise of the vehicle fleet, traffic jams, need to sort all traffic and adoption of ecologic measures to containing environmental problems. Once the system is balanced and stable, it will enable comfort, order and reduce harm to the population and region.